Determinstic Modeling of Effect of HIV Screening Postioned for Sysmptomatic HIV Individuals: An Intervention for HIV/AIDS - Ogunmola Adeniyi Oyewole; Jolayemi Emmanuel Teju (Darul Yasin Al Sys, 2025)
Literatures abound about the negative effects of the late detection of the Human Immuno-Deficiency Virus (HIV) on the effective screening and treatment of infected persons resulting in high number of mortality cases. For this study, Deterministic models to determine the effect of HIV screening at the symptomatic stage as HIV intervention was developed and evaluated. Result showed that HIV screening stationed at the hospital for HIV individuals at the symptomatic stage have the potential of reducing mortality due to AIDS, the higher the number of individuals detected in the symptomatic stage, the lower the mortality due to the infection. Based on this, early intervention where the HIV screening is taken out in search of those who have the infection and are at asymptomatic stage of the infection, may lead to reduced mortality due to the disease and its morbidity.